2021
DOI: 10.1111/1759-7714.14164
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for synchronous multiple primary lung cancer: Is it possible to achieve both curability and preservation of the pulmonary function?

Abstract: Background With the advent of high‐resolution chest imaging, the number of patients diagnosed with multiple primary lung cancers is increasing. For the treatment of multiple lung cancers, a surgical procedure that preserves pulmonary function while ensuring curability is required. Methods The study population included 85 patients with synchronous multiple primary lung cancer who received surgical resection between January 2010 and September 2020. Patients with synchronous lung cancer within the same lobe were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies have shown that patients with bilateral lung cancer can benefit more from one-stage bilateral resection than those receiving one side surgery combined with contralateral chemotherapy or radiotherapy. 23 , 24 What is more, several studies have shown that simultaneous bilateral UVATS is safe and feasible, as well as does not increase the risk of perioperative surgery. 7 , 8 As one of the largest centers for thoracoscopic surgery, our center has accumulated rich experience in simultaneous bilateral UVATS, including wedge resection, segmentectomy or lobectomy on each side.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients with bilateral lung cancer can benefit more from one-stage bilateral resection than those receiving one side surgery combined with contralateral chemotherapy or radiotherapy. 23 , 24 What is more, several studies have shown that simultaneous bilateral UVATS is safe and feasible, as well as does not increase the risk of perioperative surgery. 7 , 8 As one of the largest centers for thoracoscopic surgery, our center has accumulated rich experience in simultaneous bilateral UVATS, including wedge resection, segmentectomy or lobectomy on each side.…”
Section: Discussionmentioning
confidence: 99%
“… 17 There are two categories of MPLC, which are classified as synchronous MPLC and metachronous MPLC based on the occurrence time of the lesion. 18 The reported rate of SMPLC ranges from 0.2% to 8%. 19 , 20 After comprehensive therapy, a second primary lung cancer known as metachromatic MPLC might develop in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Association for the Study of Lung Cancer, small and multiple ground‐glass opacities found for the first time could be considered SMPLC rather than intrapulmonary metastases 17 . There are two categories of MPLC, which are classified as synchronous MPLC and metachronous MPLC based on the occurrence time of the lesion 18 . The reported rate of SMPLC ranges from 0.2% to 8% 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…We performed a comprehensive diagnosis of metachronous multiple lung cancer by referring to the diagnostic criteria proposed by Warren et al 6 and Martini et al, 7 and the diagnostic criteria of the American College of Chest Physicians presented by Shen et al 8 In cases with no evidence of a histological diagnosis, the patient was clinically diagnosed with metachronous lung cancer on the basis of the following guidelines: (1) The radiologist diagnosed the primary lung cancer as suspicious based on the imaging findings. (2) A nodule showed a gradual growth tendency for more than 6 months after the clinical course.…”
Section: Definition Of Metachronous Lung Cancermentioning
confidence: 99%
“…The frequency of detection of metachronous multiple lung cancers has recently increased, 1,2 and one reason for this increase is the progress and spread of diagnostic imaging modalities such as chest computed tomography (CT) examination, which has increased the chances of finding multiple lung nodules. In particular, patients with interstitial lung disease (ILD) are more likely to develop lung cancer than those without ILD 3 .…”
Section: Introductionmentioning
confidence: 99%